FAKTORISASI PENJURUAN SISWA SMK TERHADAP PILIHAN PROGRAM STUDI DI PERGURUAN TINGGI - Wildan Habibi, Mohammad; Zuhrifal Ridwan Muttaqin; Nova Salwa Safitri; Nadia Falisha Aaleyah; Kalista Misioneri Br Barus (STKIP Subang, 2026)
Vocational specialization in Vocational High Schools (SMK) aims to equip students with competencies aligned with their chosen fields of expertise. However, in practice, not all students continue their higher education in study programs that are relevant to their vocational majors. Therefore, this study aims to analyze various factors influencing SMK students’ decisions in choosing university study programs, both linear and non-linear to their previous educational background. The data collection method in this research was conducted through a literature review of various relevant scientific articles. Nevertheless, several studies indicate that mismatches in study program selection are influenced by various factors, such as personal interests, family encouragement, as well as the development of information and career opportunities.